MORPHOSYNTAKTISCHE INTEGRATION VON VERBEN NEOLOGISMEN IM BEREICH DES INTERNETS IN DER DEUTSCHEN SPRACHE - I.O. Ziyadullayev (TARJIMASHUNOSLIK VA TILSHUNOSLIKNING DOLZARB MUAMMOLARI: ZAMONAVIY TENDENSIYALAR VA YONDASHUVLAR, 2025)
The article focuses on the morphosyntactic integration of internet-related verb neologisms in modern German. It discusses the theoretical aspects of neologism formation, grammatical adaptation, and syntactic behavior of English-based verbs in German. The study also analyzes the process of their Germanization and incorporation into the morphological and syntactic systems of the language.